2017
DOI: 10.5194/hess-2017-720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of young water fractions to hydro-climatic forcing and landscape properties across 22 Swiss catchments

Abstract: The young water fraction F yw , defined as the proportion of catchment outflow younger than ca. 2-3 10 months, can be estimated directly from the amplitudes of seasonal cycles of stable water isotopes in precipitation and streamflow. Thus, F yw may be a useful metric in catchment inter-comparison studies that investigate landscape and hydro-climatic controls on streamflow generation. Here, we explore how F yw varies with catchment characteristics and climatic forcing, using an extensive isotope data set from 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…Accounting for spatial variations in precipitation inputs is especially important when comparing water sample isotopic compositions (e.g., from rivers, soil, plants, and aquifers) that are collected across areas with spatially variable precipitation regimes (Allen et al, ; Bowen, ; Bowen & Wilkinson, ). Comparing those values to location‐specific inputs allows for more accurately inferring how those precipitation patterns propagate through the system of interest (von Freyberg et al, ). However, mixing of spatial and temporal signals complicates interpreting tracer values in subsurface pools that integrate over large areas and durations (Kirchner, ).…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 99%
“…Accounting for spatial variations in precipitation inputs is especially important when comparing water sample isotopic compositions (e.g., from rivers, soil, plants, and aquifers) that are collected across areas with spatially variable precipitation regimes (Allen et al, ; Bowen, ; Bowen & Wilkinson, ). Comparing those values to location‐specific inputs allows for more accurately inferring how those precipitation patterns propagate through the system of interest (von Freyberg et al, ). However, mixing of spatial and temporal signals complicates interpreting tracer values in subsurface pools that integrate over large areas and durations (Kirchner, ).…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 99%
“…The top panel presents the δ 18 O cycle amplitude describing annual variability in catchment precipitation ( y axis) and stream water ( x axis) for global catchments (all n =260 catchments reported by Jasechko et al, , are shown, even the n =6 catchments with the implausible scenario: streamflow δ 18 O cycle amplitude > precipitation δ 18 O amplitude). Reported data are derived from previously published works that report amplitudes (e.g., data from Table 3 of von Freyberg et al, ; Table 4 of Song et al, ; Table S1 of Lutz et al, ; personal communications with S. Jacobs for data in Jacobs et al, ; and personal communication with D. Clow for data in Clow et al, ). The middle panel presents a histogram of young streamflow fractions reported for n =351 catchments.…”
Section: River Water Agesmentioning
confidence: 99%
“…Young streamflow comprises ~1/3 of global streamflow (Jasechko et al, ) but varies widely among rivers (Clow et al, ; Jacobs et al, ; Jasechko, Wassenaar, & Mayer, ; Lutz et al, ; Song et al, ; Stockinger et al, , ; von Freyberg et al, ). δ 18 O‐based young streamflow fractions have been reported for n =351 catchments ( n =254 catchments by Jasechko et al, ; n =30 by Jasechko, Wassenaar, & Mayer, ; n =24 by Lutz et al, ; n =22 by von Freyberg et al, ; n =5 by Song et al, ; n =11 by Clow et al, ; n =4 by Jacobs et al, ; n =1 by Stockinger et al, ). The average young streamflow among these n =351 catchments is 22% with a median of 18%, a lower‐upper quartile range of 10‐30%, and a 10th–90th percentile range of 4‐44%.…”
Section: River Water Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…We use measurements from 12 Swiss catchments (Figure S1), composing all of the sites previously analyzed by Seeger and Weiler () and von Freyberg et al () that have at least 4 years of streamwater isotope measurements. Catchment areas ranged from 0.7 to 261 km 2 , with mean elevations from 584 to 2,369 m above sea level (Table S1).…”
Section: Methodsmentioning
confidence: 99%